„Metoda” Maciejewskiego - Kaczmarek, Wojciech (Colloquia Litteraria, 2014)
Maciejewski’s ‘Method’ The article analyses kerygmatic method of interpretation that was first employed in literary studies by professor Marian Maciejewski. Thanks to this method one can verify a text and its relation to Christianity. Kerygmatic method calls for objective preciseness in defining the level of religiosity of a given text, regardless of whether it was inspired by Christianity or natural religiosity. Maciejewski’s research, mainly his works on Mickiewicz’s poems, is still governed by the directives of historical-literary analysis, nevertheless he considers his observations within the dynamics of Christian life and not in a perspective of vaguely undefined religiosity.